Studies for Development of Regional Care System for Bedridden Elderly People in Rural Community - MATSUSHIMA, Shosui (JOURNAL OF THE JAPANESE ASSOCIATION OF RURAL MEDICINE, 1994)
With aging in progress, the increase of the elderly with disorders and their care has become a serious regional problem. To step up regional care in an efficient manner, there is the need for well-organized activities with the involvement of all sorts of local people, such as medical workers (physicians, nurses, etc.), health workers (public health nurses, home helpers, medical social workers (MSW), etc.), volunteers and other people in the neighborhood in a system of coordination with various local institutions (hospitals, general practitioners' clinics, municipalities, welfare offices, social security councils, etc.) and facilities (homes for the elderly and health service facilities for the aged). Given this necessity, I have studied the efficient way in which a regional care system ought to be and the way we should wrestle with this issue in order to upgrade the delivery of regional careto old people with disorders. In a system for the delivery of regional care, the first necessary step is to prepare a place for information and liaison among various regional institutions. In this study, it has become evident that local liaison meetings, round-table discussions and research meetings are enthusiastically held to produce significant effects. For studies on actual cases of regional care, welfare service teams for the elderly are organized, but it is necessary for them to involve field personnel, such as municipal officials, medical institution officials, murses on call, home helpers, volunteers, social security council officials, agricultural cooperative officials and workers at health service facilities fore the aged. In the process of helping at-home care, the coordination of local medical institution workers, public health nurses and officials of welfare offices is particularly required. More than anything else, it is necessary for medical institutions to have an in-house division in charge of at-home care for the offer of over-the-counter services. Presumably, there are a wide variety of forms and methods for the creation of a local network. As each district has its own conditions and circumstances, the most efficient method should be worked out for each district. With the aging of subject patients, there are sure signs of an increase in the delivery of care by nurses on call, and the responses have become all the more compolicated. The necessity of care by hospital nurses on call is greater than ever. On the other hand, there are many calls for a doctor's visit. Particularly in rural communities where enough physicians are not available, it is an urgent task to establish a system of home calls while coordinating with local general practitioners and sharing roles with them. Health service facilities for the aged play a role in supplementing care at home, but those facilities which are not established side by side with hospitals have to render on-call services, whereas when it comes to hospitals without health service facilities for the aged, it is desirable for them to establish day care facilities. Attempts are already under way at various places to integrate health, medical and welfare facilities in one area so that high hopes may be pinned on significant effects both in terms of hardware and software. In this situation, it is necessary for medical institutions to play a significant role. It is necessary to step up support to the reversion to society of people given care at home and the training of volunteers as one of those medical institutions' principal roles.